1995
DOI: 10.1021/jm00011a010
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Monoamine Oxidase (MAO)-Catalyzed Oxidation of Phenyl-Substituted 1-Methyl-4-phenoxy-1,2,3,6-tetrahydropyridine Derivatives: Factors Contributing to MAO-A and MAO-B Selectivity

Abstract: The structural parameters responsible for the substrate and inhibitor selectivities of the monoamine oxidases (MAO) A and B remain poorly understood. This situation has improved somewhat with structure-activity studies that have been performed on nuclear-substituted pargyline derivatives and 4-substituted 1-methyl-1,2,3,6-tetrahydropyridine derivatives. The results of these studies suggest that the active site of MAO-A is sterically more accommodating than the active site of MAO-B. In the present work we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…Consequently, the poor substrate properties of the 4-p-hydroxy, -amino, and -nitro derivatives 8, 17, and 18, respectively, and the 4-carbamoyloxy derivatives 35 and 36 may partially be explained in terms of unfavored polar interactions within the active site. Nevertheless, other polar derivatives (e.g., the (nitrophenoxy)-1-methyl-1,2,3,6-tetrahydropyridine derivatives) 6 show good to excellent MAO-B substrate properties suggesting that favorable electrostatic interactions also may play a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the poor substrate properties of the 4-p-hydroxy, -amino, and -nitro derivatives 8, 17, and 18, respectively, and the 4-carbamoyloxy derivatives 35 and 36 may partially be explained in terms of unfavored polar interactions within the active site. Nevertheless, other polar derivatives (e.g., the (nitrophenoxy)-1-methyl-1,2,3,6-tetrahydropyridine derivatives) 6 show good to excellent MAO-B substrate properties suggesting that favorable electrostatic interactions also may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Both flexible (one or more sp 3 -hybridized atoms) and constrained (aryl) C 4 substituents may be well tolerated by both MAO-A and MAO-B, 5 although the MAO-A active site appears to accommodate bulkier groups at C 4 better than does the active site of MAO-B. 3,6 Only substitutions at the N 1 and C 4 positions of the THP ring are tolerated, 7 and apparently, only small substituents can be accommodated at the N 1 position. On the basis of results with a limited set of compounds, Efange suggested a maximum distance of 10.23 Å between the N-methyl carbon and the farthest carbon on the C 4 substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have been reported on human MAOA, bovine MAOB, and on the two rat MAOs; using various modified inhibitors (pargyline, clorgyline) and substrate (benzylamine) analogues (7-13). The SAR studies using a series of ring substituted pargyline analogues on rat MAOA and MAOB (rMAOA and rMAOB) have shown that the position of substitution on the aromatic ring of pargyline ( meta vs. para ) influences the isoform specificities of the corresponding inhibitor analogues.…”
mentioning
confidence: 99%
“…As shown in Scheme A, the TPE based MAO probe is composed of an N -methyl phenylpyridium, a TPE fluorogen, and a C–C double bond linker. The N -methyl phenylpyridium and its analogues are unique inhibitors with high binding affinity toward both MAO-A and MAO-B. TPE, as a large substituent at 4-position of phenylpyridium, is expected to make the probe more selective toward MAO-A . The positively charged pyridium moiety is hydrophilic, which should render the probe dispersible in aqueous media, especially at low concentrations.…”
Section: Results and Discussionmentioning
confidence: 99%